Understanding Healing: A Conceptual Analysis - Akhmedova Shakhodat Makhmutovna (Periodica Journal, 2024)
The article focuses on describe the use of a rigorous methodology, concept analysis, to clarify the meaning of healing and propose an operational definition of healing in order to further the scientific understanding and translation of optimal healing environments (OHE)s into practice.
Keywords: Wholeness; language; concept; process